CHILDREN AND CHILDHOOD AS DEPICTED IN OLIVER TWIST BY CHARLES DICKENS AND HARRY POTTER SERIES BY J. K. ROWLING - Nguyen Nhat Ha (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
English literature has attracted a great deal of attention from language students and those who have the desire to study about English people, culture and history. Oliver Twist and Harry Potter Series are two of the most typical English masterpieces. Even though some previous work has been conducted to examine these two novels, the comparison of Oliver Twist and Harry Potter Series has been left untouched. This research aims to approach a shared characteristic of the two literary works: child characters and their childhood. It is expected to provide language students and those who are concerned a better insight into the image of children and childhood as reflected in literature in general and in English literature in particular.